Examining the Impact of Two Leadership Patterns on Creativity via Psychological Empowerment in Indonesian Service and Banking Sectors - Ramadhani, Aldi; Pradana, Handrio Adhi (Jurnal Ecogen, 2024)
With the lens of sensemaking theory, this research aims to examine the effect of transformational and transactional leadership on employee creativity with psychological empowerment acting as a mediator. This research used quantitative methods with primary data sources. Data was collected by designing in such a way and distributing questionnaires via online. The sample size in this research was 157 respondents who work in various industries such as services, manufacturing, educational institutions, and banking. The data analysis used multiple linear regression and mediating testing procedure by Preacher and Hayes. The results showed that transformational leadership, transactional leadership, and psychological empowerment had a significant positive effect on creativity. Transformational and transactional leadership have a significant positive effect on psychological empowerment. Psychological empowerment succeeded in being mediator for the two different leadership styles in nature, that are transformational and transactional leadership, influencing on creativity. This research contributes to the development of literature on two types of leadership at once, namely transformational and transactional. So far, transactional leaders are considered to have a negative effect on outcome variables. However, this research is able to reveal the same capability between transformational and transactional in improving employee performance particularly in emerging country context.